2008
DOI: 10.3998/ark.5550190.0009.216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of some derivatives of acylhydrazine including novel benzenediazasulfonamides

Abstract: Some novel derivatives of acylhydrazine such as; 5-substituted-2-mercapto-1,3,4-oxadiazoles 2a-g their corresponding S-esters 3a-g, amides 4a-g and benzenediazasulfonamides 6a-d have been prepared. Twenty four synthesized compounds were screened in vitro for their antibacterial and some for their antifungal activities. Minimum Inhibitory Concentration (MIC) values of all the twenty four synthesized compounds were also determined. Some of the synthesized compounds exhibited significant antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Similarly, the scope of the aniline proved that the substitution pattern (meta-or paramethyl, 19 and 20, respectively, Figure 2) did not affect the reaction efficiency. However, while electron-rich N,Ndimethylanilines were shown to be suitable starting materials (21), the presence of an electron-withdrawing atom, such as chlorine, led to a modest 23% yield (22). Interestingly, regioselectivity for -CH3 oxidation was observed when N-ethyl-Nmethylaniline was used as the starting amine component (23, Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the scope of the aniline proved that the substitution pattern (meta-or paramethyl, 19 and 20, respectively, Figure 2) did not affect the reaction efficiency. However, while electron-rich N,Ndimethylanilines were shown to be suitable starting materials (21), the presence of an electron-withdrawing atom, such as chlorine, led to a modest 23% yield (22). Interestingly, regioselectivity for -CH3 oxidation was observed when N-ethyl-Nmethylaniline was used as the starting amine component (23, Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…More in detail, the 1,3,4-oxadiazole derivative 7 was formed according to standard reaction conditions (Table 1, entry 12); subsequent in situ addition of HCl 6N (final concentration 1:1 v/v with respect to the standard reaction solvent), at room temperature, led, after 20 hours, to the hydrolysis of the heterocyclic core thus providing a facile and expeditious access to such pharmaceutically relevant scaffolds (Figure 2). [20][21][22] It is worth noting that a representative synthesis of scaffolds similar to 26 has been reported in three steps with overall yields of ~ 29%. 23…”
Section: Figure 2 Reaction Scope (Standard Reaction Conditions As In Table 1 Entry 12)mentioning
confidence: 99%
“…Chromatography of the residue on 50 g of silica gel eluting with diethyl ether/hexane (1:1) afforded bicyclic ketone 8 (95%, 40 mol, 4.88 g) as a pale yellow viscous oil. 20 Bicyclo[4.2.0]oct-3-en-7-one (8)…”
Section: Reduction Of 88-dichlorobicyclo[420]oct-3-en-7-one(7)mentioning
confidence: 99%
“…[2][3][4][5][6][7] In 2008, Zareef et al synthesized some derivatives of acylhydrazine including benzene diazasulfonamides and newly synthesized molecules were screened in vitro for their antibacterial activity and some for their antifungal activity. 8 Balemans et al identified new diarylquinoline drug candidates (3) with inhibitory activity against gram-positive pathogens and rapid bactericidal activity on S.aureus in 2012. 9 Organohalogen molecules frequently display the highest level of biological activity.…”
Section: Introductionmentioning
confidence: 99%